Penggunaan Multimedia Presentasi pada Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Kemampuan Menulis Peserta Didik (Studi Kasus Pada Tema Ekosistem di Kelas 5 SDN 6 Cikondang) - De Budi Irwan Taofik; Aceng Ahmad Rodian Susila (Institut Pendidikan Indonesia, 2022)
The research is aim to know raising student competence in writing using project based learning model based mutimedia presentation. This method research using experiment method with quantitative approach. Design is used experimental formed nonequivalence design group pretest-posttes. Research approach can summarised are: 1) Student writing competence raise after learning using projects based learning base mutimedia presentation in Bahasa Indonesia learning to student at grade five SDN 6 Cikondang and 2) there are different result of writing study in bahasa indonesia at grade five SDN 6 Cikondang between student who use project based learning base mutimedia presentation and student who don't use it.